A revision of the genus Goniusa Casey, 1906 (Coleoptera: Staphylinidae: Aleocharinae) - Gusarov, Vladimir I. (Zootaxa, 2003)
Nearctic genus Goniusa Casey, 1906 is redescribed and placed in the tribe Athetini Casey, 1910. Goniusa obtusa sensu Casey, 1906 (nec LeConte, 1866) is a misidentification. Goniusa caseyi Gusarov, sp. n. (from Massachusetts, New Hampshire, New York, New Jersey, District of Columbia, Texas and Manitoba) is described for G. obtusa auct., nec LeConte, 1866. Goniusa caseyi is fixed as the type species of Goniusa under provisions of the Article 70.3 of the Code. A key for identification of species of Goniusa is provided. Euryusa obtusa LeConte, 1866 is transferred to the genus Lypoglossa Fenyes, 1918.